Forestry research, innovation and impact in developing countries - from economic efficiency to the broader public good - Spilsbury, M.J.; Kaimowitz, D. (2002)
This paper applies a broad-brush perspective to forestry research, innovation and research capacity in developing countries and the impacts linked to it. The authors reflect upon successes and failures in the hope of improving the focus and relevance of future efforts and highlight emerging research approaches aimed at ameliorating some of the deficiencies. They begin by examining the role of informal research and the emergence of formal research in developing countries. They note that for most of the last century, forestry research was predominantly focussed on achieving “efficiency gains” in forest production systems, and that this focus was shared by both private enterprise and prevailing approaches to broader “development” in developing countries. They assert that there has been difficulty in realising research-induced efficiency gains in the developing tropics and suggest that the underlying reasons often relate to insecure land tenure, resource, conflicts, lack of access to capital, large power imbalances and corruption within society. Changing research priorities are increasingly directed towards improvement of rural livelihoods in the context of sustainable resource management. They observe that forestry-related research capacity in developing countries is weak and under-resourced and there is commonly a mismatch between the skills available in the “installed capacity” of public sector research institutions and those required for the topics that have the highest potential to generate public goods. The authors propose that the focus should place a greater emphasis on policy research to relieve the constraints highlighted above and believe that impact can be enhanced through integrated “action research” across disciplines, scales and stakeholders.